Reporting of Research Ethics in Studies Focusing on Foot Health in Patients with Rheumatoid Arthritis - A Systematic Review - Stolt Minna; Kielo-Viljamaa Emilia; Laitinen Anne-Marie; Suhonen Riitta; Leino-Kilpi Helena (SAGE PUBLICATIONS INC, 2022)
Research ethics is a fundamental part of the entire research. Patients with rheumatoid arthritis are sensitive group of research participants because their long-term health problems cause significant changes in their foot health. In foot health research, data are usually collected through a clinical assessment of the foot or questionnaires. However, there is limited evidence of the reported research ethics of empirical studies on foot health in patients with rheumatoid arthritis. Therefore this review aimed to analyze the reported research ethics of peer-reviewed empirical studies focusing on foot health in patients with rheumatoid arthritis as research participants. This systematic review used the Medline/PubMed, CINAHL, and Embase databases. A total of 1,653 records were identified, and 32 articles were included in the final analysis. Reporting research ethics in studies of patients with rheumatoid arthritis is fragmented, focusing predominantly on ethical approval and informed consent and lacking a broader discussion about research ethics.